Health Care Experiences of Black Transgender Women and Men Who Have Sex With Men: A Qualitative Study. (July 2020) - Salerno, John P.; Turpin, Rodman; Howard, Donna; Dyer, Typhanye; Aparicio, Elizabeth M.; Boekeloo, Bradley O.
Abstract: Black sexual and gender minorities (SGM) are at greater risk for HIV compared to their White, cisgender, heterosexual counterparts. Linkage to culturally sensitive health care is, therefore, pivotal for HIV prevention and treatment of Black SGM. Unfortunately, social and structural challenges undermine Black SGM individuals' abilities to obtain adequate health care services, indicating a need to understand Black SGM perceptions of health care. To address this gap, we interviewed Black men who have sex with men and transwomen about their experiences with health care providers. Participants discussed needs and concerns, including provider SGM identity diversity and education; assumptions, judgment, stigma, and discrimination; and ability to establish a personal bond, trust, and familiarity. Black SGM indicated that providers often did not meet their needs in different ways regarding their SGM identities. Findings suggest a need for provider cultural sensitivity education programs that address the needs of Black SGM in health care.